(untitled) (TAJ: Journal of Teachers Association, 2018)
Renal tubular acidosis (RTA) is caused by defect in renal tubular acid transport. Sjogren’s syndrome, rheumatoid arthritis, systemic lupus erythematosus and autoimmune hepatitis are the most common autoimmune causes of distal RTA. We are reporting a case of distal renal tubular acidosis associated with mixed connective tissue disease and hypothyroidism presenting as recurrent hypokalemic paralysis. TAJ 2017; 30(2): 76-78